An oxygen-passivated vanadium cluster [V@V10O15]− with metal–metal coordination produced by reacting Vn− with O2. Issue 2 (22nd December 2020) - Zhang, Hanyu; Cui, Chaonan; Yan, Miao; Geng, Lijun; Wu, Haiming; Jia, Yuhan; Luo, Zhixun; Li, Si-Dian
Abstract : An oxygen-passivated vanadium cluster [V@V10 O15 ] − is reported by reacting V n − with O2, giving rise to superatom features of metal–metal coordination and 3D aromaticity. Abstract : Vanadium cluster anions are highly reactive making the preparation of pure V n − and the observation of their reactivity extremely challenging. Herein, well-resolved anionic V n − clusters are prepared enabling an in-depth study on their reactions with O2 in the gas phase. While pure metal clusters of a magic number are not identified due to the strong V–O bonding, interestingly an unexpected oxide V11 O15 − was experimentally observed in surviving O2 etching reactions. First-principles theory calculations indicate that V11 O15 − possesses a body-centered pentagonal prism structure ( D 5 h, ), with the V@V10 core fully protected by 15 oxygen bridges. Such an oxygen-protected metal cluster [V@V10 O15 ] − exhibits typical superatom orbital features pertaining to the V@V10 core which shows effective metal–metal coordination bonding. Meanwhile, the high stability of [V@V10 O15 ] − is reinforced by the V–O–V conjugation interactions which help to maintain the structural integrity, resulting in 3D inorganic aromaticity. This finding of such an oxygen-passivated superatom cluster sheds light on the bonding nature in ligand-protected metal clusters via wet synthesis.